ABA-dependent suberization and aquaporin activity in rice (Oryza sativa L.) root under different water potentials - Kim, Ga-Eun; Sung, Jwakyung (Frontiers in Plant Science, 2023)
Drought is one of the most stressful environments limiting crop growth and yield throughout the world. Therefore, most efforts have been made to document drought-derived genetic and physiological responses and to find better ways to improve drought tolerance. The interaction among them is unclear and/or less investigated. Therefore, the current study is to find a clue of metabolic connectivity among them in rice root experiencing different levels of drought condition. We selected 19 genes directly involved in ABA metabolism (6), suberization (6) and aquaporins (AQPs) activity (7), and analyzed the relatively quantitative gene expression using qRT-PCR from rice roots. Besides, we also analyzed proline, chlorophyll and fatty acids, and observed cross-sectional root structure (aerenchyma) and suberin lamella deposition in the endodermis. All drought conditions resulted in an obvious development of aerenchyma and 2 to 4-fold greater accumulation of proline. The limited water supply (-1.0 and -1.5 MPa) significantly increased gene expression (ABA metabolism, suberization and AQPs), and developed greater layer of suberin lamella in root endodermis. In addition, the ratio of the unsaturated to the saturated fatty acids was increased, which could be considered as an adjusted cell permeability. Interestingly, these metabolic adaptations were an exception with a severe drought condition (hygroscopic coefficient, -3.1 MPa). Accordingly, we concluded that the drought-tolerant mechanism in rice roots is sophisticatedly regulated until permanent wilting point (-1.5 MPa), and ABA metabolism, suberization and AQPs activity might be independent and/or concurrent process as a survival strategy against drought.